Analyzing the Safety and Efficacy of Flow-Diverting Stents in Pediatric Aneurysms: A Systematic Review. Issue 2 (7th April 2021) - Scoville, Jonathan; Joyce, Evan; Baker, Cordell; Dewey, Jesse; Grandhi, Ramesh; Taussky, Philipp
Abstract: Ruptured intracranial aneurysms cause 50% of spontaneous subarachnoid hemorrhages in children, resulting in up to 65% mortality when left untreated. Although flow-diverting stents are especially suited to treat the fusiform and giant aneurysms more commonly found in children, the US Food and Drug Administration (FDA) has only approved their use in patients ≥22 years of age. Our objective was to assess the safety of flow-diverting stents in the treatment of pediatric patients with aneurysms through a systematic literature review using the PRISMA criteria. We used PubMed, Embase, and Web of Science to identify all published cases of pediatric aneurysms treated or retreated using flow-diverting stents from 2007 through 2019. Two independent researchers developed a consensus regarding the inclusion of all articles. Patient data were extracted from the identified articles and used to calculate the incidence rate of complications. From 1396 journal articles identified, 24 articles contained data on 37 pediatric patients that met the inclusion criteria. Of these 37 patients, 8 (21.6%) had a complication by last follow-up (death: 2; residual aneurysm: 2; parent artery occlusion: 4). This resulted in an incidence rate of 0.018 complications per patient at-risk month (95% CI 0.008-0.035). These data suggest that the use of flow-diverting stents for treatment of aneurysms in children may be safe and that FDA approval for this use should be evaluated. Although this analysis is comprised of case reports and case series, it represents the best attempt thus far to quantify the risk of using flow-diverting stents in children.